X‐box binding protein 1 (XBP1) function in diseases. (25th December 2020) - Xu, Wenjing; Wang, Congrong; Hua, Jinlian
Abstract: The accumulation of unfolded or misfolded proteins in the endoplasmic reticulum (ER) causes endoplasmic reticulum stress (ERS), which is characteristic of cells with high levels of secretory activity and is involved in a variety of diseases. In response to ERS, cells initiate an adaptive process named the unfolding protein response (UPR) to maintain intracellular homeostasis and survival. However, long term and unresolved ERS can also induce apoptosis. As the most conserved signaling branch of UPR, the IRE1‐XBP1 pathway plays an important role in both physiological and pathological states, and its activity has a profound impact on disease progression and prognosis. Here, the latest research progress of IRE1‐XBP1 pathway in cancer, metabolic diseases, and other diseases was briefly introduced, and the relationship between several diseases and this pathway was analyzed. Besides, the new understanding and prospect of IRE1‐XBP1 pathway regulating male reproduction were reviewed.